2003
DOI: 10.1002/ajmg.a.20021
|View full text |Cite
|
Sign up to set email alerts
|

Stocco dos Santos X‐linked mental retardation syndrome: Clinical elucidation and localization to Xp11.3–Xq21.3

Abstract: Mental retardation (MR) affects an estimated 2-3% of the population. A considerable fraction of mental retardation is due to X-linked genes. Of these genes, about 136 are responsible for syndromic X-linked MR (XLMR). One such XLMR syndrome, Stocco dos Santos, was first described in 1991. This family was re-visited, which allowed further delineation of the clinical phenotype. Additionally, linkage analysis was conducted, which resulted in the localization of this XLMR syndrome to the pericentric region, Xp11.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…These findings suggest that disruption of hKIAA1202 is causative for the shared clinical features, which include mental delay. Moreover, we identified a c.1422A>G exchange, not detected in 1,266 control X-chromosomes, segregating in a small family, and a c.3266C>T transition, not found in 1,021 control X-chromosomes, which segregates with the Stocco dos Santos XLMR syndrome in a large fourgeneration family (Stocco dos Santos et al 2003). Finally, we have shown that hKIAA1202 and its mouse homologue mKiaa1202 are expressed in adult and foetal brain.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These findings suggest that disruption of hKIAA1202 is causative for the shared clinical features, which include mental delay. Moreover, we identified a c.1422A>G exchange, not detected in 1,266 control X-chromosomes, segregating in a small family, and a c.3266C>T transition, not found in 1,021 control X-chromosomes, which segregates with the Stocco dos Santos XLMR syndrome in a large fourgeneration family (Stocco dos Santos et al 2003). Finally, we have shown that hKIAA1202 and its mouse homologue mKiaa1202 are expressed in adult and foetal brain.…”
Section: Discussionmentioning
confidence: 70%
“…Their mothers also have experienced seizures and periods of depression. Although XCI studies in peripheral blood of all obligate carriers showed skewed inactivation in excess of 90:10 (Stocco dos Santos et al 2003), it is possible that a remaining small amount of mutant protein exerts its influence in a dominant negative way, leading to their moderate phenotype. Alternatively, the XCI pattern at the hKIAA1202 locus may be variable during development or could be tissue specific (Sheardown et al 1996).…”
Section: Genomic Organisation Of Hkiaa1202mentioning
confidence: 99%
“…The SYP gene is the strongest candidate for the seizures observed in these patients as loss or mutations in this gene have been associated with seizures [Tarpey et al, 2009]. Seizures are also a feature of Stocco dos Santos syndrome [Stocco dos Santos et al, 2003], which is caused by mutations in the SHROOM4 (OMIM*300579) gene (∼50.4 Mb, Fig. 3) [Hagens et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the PQBP1 gene, multiple other genes are duplicated within this 4.7 Mb region and may contribute to our patient's phenotype. Mutations in the SHROOM4 gene have been linked to Stocco dos Santos X‐linked mental retardation syndrome, which is characterized by severe intellectual disability, bilateral congenital hip dislocation, and short stature [Stocco dos Santos et al, 2003]. Mutations in the FTSJ1 gene are a cause of non‐syndromic X‐linked moderate–severe intellectual disability [Froyen et al, 2007].…”
Section: Discussionmentioning
confidence: 99%